2016
DOI: 10.1016/j.ccell.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dopamine Receptor D4 Impedes Autophagic Flux, Proliferation, and Survival of Glioblastoma Stem Cells

Abstract: SUMMARY Glioblastomas (GBM) grow in a rich neurochemical milieu, but the impact of neurochemicals on GBM growth is largely unexplored. We interrogated 680 neurochemical compounds in patient-derived GBM neural stem cells (GNS) to determine the effects on proliferation and survival. Compounds that modulate dopaminergic, serotonergic, and cholinergic signaling pathways selectively affected GNS growth. In particular, dopamine receptor D4 (DRD4) antagonists selectively inhibited GNS growth and promoted differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
149
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(163 citation statements)
references
References 47 publications
11
149
1
2
Order By: Relevance
“…Low-grade glioma-bearing mice treated with the tricyclic antidepressant imipramine exhibited prolonged survival, with decreased rate of tumor cell proliferation and reduced progression to high grade lesions; the mechanism of action appears to involve induction of autophagy, leading to apoptosis (Shchors et al, 2015). Glioblastoma cells express dopamine receptors (Dolma et al, 2016; Li et al, 2014), and in a proliferation screen performed on three patient-derived glioma cell cultures exposed to a panel of neurotransmitter agonists, antagonists, and reuptake inhibitors, pharmacologic blockade of dopamine receptor D4 emerged as an effective and selective inhibitor of glioma cell proliferation via disruption of autophagy and downstream induction of apoptosis (Dolma et al, 2016). Glioma cells also express functional serotonin receptors (Mahe et al, 2004), but whether serotonergic signaling influences glioma growth or progression is less clear, as increased serotonin levels as a result of selective serotonin reuptake inhibitor (SSRI) therapy have not been shown to have a survival benefit in retrospective studies of patients with glioblastoma and comorbid depression (Caudill et al, 2011).…”
Section: Neurotransmitters and Glioma Growth And Progressionmentioning
confidence: 99%
“…Low-grade glioma-bearing mice treated with the tricyclic antidepressant imipramine exhibited prolonged survival, with decreased rate of tumor cell proliferation and reduced progression to high grade lesions; the mechanism of action appears to involve induction of autophagy, leading to apoptosis (Shchors et al, 2015). Glioblastoma cells express dopamine receptors (Dolma et al, 2016; Li et al, 2014), and in a proliferation screen performed on three patient-derived glioma cell cultures exposed to a panel of neurotransmitter agonists, antagonists, and reuptake inhibitors, pharmacologic blockade of dopamine receptor D4 emerged as an effective and selective inhibitor of glioma cell proliferation via disruption of autophagy and downstream induction of apoptosis (Dolma et al, 2016). Glioma cells also express functional serotonin receptors (Mahe et al, 2004), but whether serotonergic signaling influences glioma growth or progression is less clear, as increased serotonin levels as a result of selective serotonin reuptake inhibitor (SSRI) therapy have not been shown to have a survival benefit in retrospective studies of patients with glioblastoma and comorbid depression (Caudill et al, 2011).…”
Section: Neurotransmitters and Glioma Growth And Progressionmentioning
confidence: 99%
“…Based on the unique capability of the D 4 receptor to modulate methylation status, we suggest that the anti-glioblastoma tumor effects of D 4 receptor antagonists described by Dolma et al (12) may reflect inhibition of methylation reactions such as dopamine-stimulated PLM, which can influence the activity of receptors and transporters at the plasma membrane (80), and/or SAM-dependent methylation effects, which might include effects on autophagy. For example, increased membrane fluidity and/or membrane asymmetry promoted by D 4 receptor-mediated PLM may contribute to PDGFRβ transactivation.…”
Section: D4 Receptors Methylation and Glioblastomamentioning
confidence: 88%
“…Dolma et al (12) recently reported that selective D 4 receptor antagonists restrict the growth of glioblastoma stem cells in vitro and in vivo . Clonogenic activity of freshly isolated tumor cells was reduced 19- to 83-fold by these antagonists.…”
Section: D4 Receptors Methylation and Glioblastomamentioning
confidence: 99%
See 2 more Smart Citations